2014
DOI: 10.3109/07435800.2013.879165
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin receptor 1 overexpression reduces lipid accumulation and hypertrophy in the heart of diet-induced obese mice – possible involvement of oxidative stress and autophagy

Abstract: The AdipoR1 transgene enabled mice to resist diet-induced obesity while decreasing lipid accumulation, oxidative stress and autophagic damage. These effects might contribute to the improvement of heart functions in diet-induced obese mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…When adiponectin binds to its receptors (Adipor1/2), it activates adenosine 5`-monophosphate-activated protein kinase (AMPK), promoting glucose uptake by skeletal muscle via intracellular translocation of the glucose transpoter type 4 (GLUT4). Animal studies showed that Adipor1 transgene mice enabled mice to resist high fat/high sucrose diet-induced obesity while decreasing lipid accumulation [23]. We found that in mature F442A adipocytes, GH treatment increased the abundance or availability of adiponectin receptors, and increased adiponectin protein expression.…”
Section: Gh Modulates the Expression Of Genes Related To Lipolysis Inmentioning
confidence: 59%
“…When adiponectin binds to its receptors (Adipor1/2), it activates adenosine 5`-monophosphate-activated protein kinase (AMPK), promoting glucose uptake by skeletal muscle via intracellular translocation of the glucose transpoter type 4 (GLUT4). Animal studies showed that Adipor1 transgene mice enabled mice to resist high fat/high sucrose diet-induced obesity while decreasing lipid accumulation [23]. We found that in mature F442A adipocytes, GH treatment increased the abundance or availability of adiponectin receptors, and increased adiponectin protein expression.…”
Section: Gh Modulates the Expression Of Genes Related To Lipolysis Inmentioning
confidence: 59%
“…Since our first report of increased cardiac autophagy in the type 2 diabetic fructose-fed mouse (59), the experimental literature in this field has expanded considerably, but it is not yet possible to synthesize a comprehensive understanding. Relying on a variable selection of molecular tools, states of increased (4,12,49,50,59,61,78,93,102), unchanged (47,48,57,62), and decreased (6,23,28,29,73,82,101,103,104,110) basal cardiac autophagy activity have all been reported in diabetic/ insulin resistant contexts (see Table 1). These discrepancies are not necessarily attributable to the different models of diabetes, since contrasting findings have been observed within the same diabetic model [e.g., STZ-mouse: increased LC3BII (12) vs. decreased LC3BII (103)].…”
Section: )mentioning
confidence: 99%
“…AdipoR is cell autonomously required for GSC maintenance (Fig. 4), and overexpression of adiponectin receptors has been shown to enhance adiponectin signaling in mammals (Chou et al, 2014; Luo et al, 2013). We therefore wondered if increasing the expression of AdipoR in the germline might counteract the normal process of GSC loss over time.…”
Section: Resultsmentioning
confidence: 99%